Hepatosteatosis: 100 cases - İbrahim Halil BAHÇECİOĞLU and Hakan ŞENTÜRK and Ali MERT and Gürkan BAŞARAN and Mesut AKÇAKAYA and İbrahim KELEŞ and Fehmi TABAK and Mahmut İLHAN and; han AKIN and; en ÖZBAY (Turkish Journal of Gastroenterology, 2019)
-